MODELING OF THE PROCESS OF PREPARING FUTURE TEACHERS OF INFORMATICS TO RESOURCE-SAVING ACTIVITIES BASED ON EUROPEAN EXPERIENCE - Ekaterina A. Konopko; Olga P. Pankratova (Международный научный журнал "Современные информационные технологии и ИТ-образование", 2017)
The article describes the model for the preparation of future teachers of informatics for resource-saving activities, the stages of modeling are considered. The developed model, which is a structural interconnection of the target, content, technological, technical and effective components, will allow not only to form the teachers' readiness for introduction of innovative teaching methods in the educational process of the school on the basis of green information technologies, but also to develop a culture of resource saving. В статье приводится описание модели подготовки будущих учителей информатики к ресурсосберегающей деятельности, рассмотрены этапы моделирования. Разработанная модель, представляющая собой структурную взаимосвязь целевого, содержательного, технологического, технического и результативного компонентов, позволит не только сформировать у педагогов готовность к внедрению в образовательный процесс школы методов инновационного обучения на основе зеленых информационных технологий, но и развить у них культуру ресурсосбережения.